2019
DOI: 10.1128/mcb.00020-19
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Independence 1B-Mediated Transcriptional Repression and Lineage Allocation Require Lysine-Specific Demethylase 1-Dependent Recruitment of the BHC Complex

Abstract: Growth factor independence 1B (GFI1B) coordinates assembly of transcriptional repressor complexes comprised of corepressors and histone-modifying enzymes to control gene expression programs governing lineage allocation in hematopoiesis. Enforced expression of GFI1B in K562 erythroleukemia cells favors erythroid over megakaryocytic differentiation, providing a platform to define molecular determinants of binary fate decisions triggered by GFI1B. We deployed proteome-wide proximity labeling to identify factors w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 99 publications
(118 reference statements)
2
27
0
Order By: Relevance
“…3A, Table S1). This is in line with the evidence that GSE1 is mainly associated with co-repressor complexes, such as the HDAC2 and BHC complexes 35,37 . Intersecting the differentially expressed genes (DEG) in common between the two KD conditions, we obtained 422 common up-regulated and 47 common down-regulated genes (Fig.…”
Section: Reducing Gse1 Protein Level In Aml Lsd1 Inhibitors Promote supporting
confidence: 90%
See 1 more Smart Citation
“…3A, Table S1). This is in line with the evidence that GSE1 is mainly associated with co-repressor complexes, such as the HDAC2 and BHC complexes 35,37 . Intersecting the differentially expressed genes (DEG) in common between the two KD conditions, we obtained 422 common up-regulated and 47 common down-regulated genes (Fig.…”
Section: Reducing Gse1 Protein Level In Aml Lsd1 Inhibitors Promote supporting
confidence: 90%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted February 16, 2021. ; https://doi.org/10.1101/2021.02.16.431315 doi: bioRxiv preprint 5 GSE1 in neuro-epithelial stem (NES) cells 33 . GSE1 effect in haematological malignancies and AML in particular has not been investigated yet, especially in the context of its physical and functional interaction with LSD1 [34][35][36][37] .…”
mentioning
confidence: 99%
“…Finally, we and others showed that many proteins associate with CoREST in the context of GFI1/1B (32, 35, 57). Although the effect on CoREST function has been studied for some of these factors, the role of others like ZNF217, and PHF21A is still unclear.…”
Section: Future Perspectivesmentioning
confidence: 60%
“…At the N-terminus of the proteins, there is a highly conserved SNAIL/ GFI1 (SNAG) domain that is present in both GFI1 and GFI1B with ~90% homology, forming a sub-family on their own. This domain is shared with other transcriptional repressors such as SNAIL, SCRATCH, and SLUG forming a distinct but larger SNAG protein sub-family (Grimes et al, 1996;Manzanares et al, 2001;Katoh andKatoh, 2003, andreviewed in Chiang andAyyanathan, 2013) and mediates transcriptional repression by recruiting chromatin modifier complexes to the regulatory regions of GFI1/GFI1B target genes (Tong et al, 1998;Saleque et al, 2007;Velinder et al, 2016;McClellan et al, 2019).…”
Section: Introduction Gfi1 and Gfi1b As Transcription Factorsmentioning
confidence: 99%